The effects of solar flares on the very low frequency signals recorded by super SID system - Canyilmaz, M.; Guzel, E.; Akdogan, T. (Allerton Press Inc, 2016)
Solar flares cause sudden disturbances at the Earth's ionosphere. These effects are detected by the very low frequency (VLF), 3-30-kHz signals which are propagated at the Earth-ionosphere waveguide. The sudden changes on the time-dependent intensity of VLF signals are recorded by Super SID system during February, March, and April, 2013. Then VLF data were compared with the GOES satellite data found in the Space Environment Center online database. The main factors of the variation in VLF signal intensities recorded by the Super SID system are class, duration of the solar flare and the frequency of VLF signals.
Keywords: Ihy